BANTEN LAMA LANDMARK BASED ON VISITORS PERCEPTION - Sangiru Kasmo Suweko; Maria Immaculata Ririk winandari; Etty Retnowati Kridarso (International Journal on Livable Space, 2018)
Old Banten Region is an area that is famous for trading at its time. Currently, related to the past glory this place turn into a religious tourist destination .There are still many relics of ancient buildings which show the image of the past glory as well as the element of the city image in Old Banten Region . This study has aim to explore the image of the city of Banten Lama based on visitors' visual perception. The research method uses visual perception method with a rating rating of 14 Landmarks (tetenger) selected based on case selection. Respondents consisted of 40 visitors. The results showed that the image of Banten Lama area based on visual perception of visitors was built based on the image of Banten Lama Great Mosque at 39.63%, Avalokitesvara Vihara 16.16% and Surosowan palace 9.76%.